Surface-controlled spatially heterogeneous physical properties of a supramolecular gel with homogeneous chemical composition. Issue 42 (20th October 2021) - Yang, Bin; Lledos, Marina; Akhtar, Riaz; Ciccone, Giuseppe; Jiang, Long; Russo, Emanuele; Rajput, Sunil; Jin, Chunyu; Angelereou, Maria Galini Faidra; Arnold, Thomas; Rawle, Jonathan; Vassalli, Massimo; et al.
Abstract : A mechanical pattern is created in a hydrogel film by pre-patterning the underlying surface chemistry. This allows spatial variation of the viscous component of the gel, controlling dissipative forces in the gel film without altering gel chemistry. Abstract : Controlling supramolecular self-assembly across multiple length scales to prepare gels with localised properties is challenging. Most strategies concentrate on fabricating gels with heterogeneous components, where localised properties are generated by the stimuli-responsive component. Here, as an alternative approach, we use a spiropyran-modified surface that can be patterned with light. We show that light-induced differences in surface chemistry can direct the bulk assembly of a low molecular weight gelator, 2-NapAV, meaning that mechanical gel properties can be controlled by the surface on which the gel is grown. Using grazing incidence X-ray diffraction and grazing incidence small angle X-ray scattering, we demonstrate that the origin of the different gel properties relates to differences in the architectures of the gels. This provides a new method to prepare a single domain ( i.e., chemically homogeneous) hydrogel with locally controlled ( i.e., mechanically heterogeneous) properties.